Ciklični preizkusi armiranobetonskih stebrov - Kramar, Miha (Gradbeni vestnik, 2016)
The paper presents an experimental study of seismic resistance of reinforced concrete columns for the purpose of analysing the influence of uncertainty of material characteristics and uncertainty in manufacture. In order to cover all of the considered sources of uncertainty, 12 columns were manufactured in three different companies. The same plan and nominally the same materials were used in the production of the columns. In addition to the material characteristics, the influence of lapping of longitudinal reinforcement on the seismic response of columns was analysed as well. The columns were tested with cyclic horizontal load, which was increased until collapse. The research has shown that there are big differences in the manufacture of the columns, which is observed in the seismic response after reaching the maximum capacity. The biggest influence on the ductility can be attributed to the detailing of the stirrups. The research has also confirmed some already well-known dependences and demonstrated that one of important parameters of the seismic resistance of columns might be the location of the first stirrup above the foundation.
Keywords: armiranobetonski steber; ductility; duktilnost; negotovosti; nosilnost; potresni odziv; reinforced concrete column; seismic response; stirrups; stremenska armatura; strength; uncertainty